Do emotional carryover effects carry over? - Nikhil Masters; Tim A. Lloyd; Chris Starmer (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2022)
Existing research has demonstrated carryover effects whereby emotions generated in one context influence decisions in other, unrelated ones. We examine the carryover effect in relation to valuations of risky and ambiguous lotteries with a novel focus on comparing the carryovers arising from a targeted stimulus (designed to elicit a specific emotion) with those arising from a naturalistic stimulus (expected to produce a more complex emotional response). We find carryover effects using both a standard targeted stimulus and a naturalistic one, but they are stronger for the naturalistic stimulus and in the context of ambiguity. These effects are also highly gender-specific with only males being susceptible. To probe the emotional foundations of behaviour, we conduct analysis relating individual self-reports of emotions to incentivised valuation behaviour. Our results cast doubt on the interpretation of some evidence purporting to establish links between specific incidental emotions and risk taking.
Keywords: C91; D81; D91; 330; Incidental emotions; Emotional carryover; Risk; Ambiguity; Naturalistic; Structural equation modelling